The Role of Communication in Health Services in Indonesia - Cut Khairunnisa; masriadi, masriadi; Mohd Zamre Mohd Zahir; Muhammad Hatta; Nurarafah (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2023)
In the principle of informed consent, doctors were obliged to establish communication with patients before carrying out medical treatments. Information from the doctor became a guideline or consideration for patients in making a choice (freedom to choose) and gave approval to the doctor to carry out medical action to them. The obligation of doctors to effectively communicate has been regulated in Article 35 and Article 45 of Law No. 29 of 2004 concerning Medical Practice and further strengthened by Regulation of the Minister of Health of the Republic of Indonesia No. 290/ Menkes/ Per/ III/ 2008 concerning Approval of Medical Measures. The effectiveness of communication in health services was an act of caution in medical treatments. Before the medical treatment was carried out, the patient should already knew about the disease, the chances of healing, the risk of medical treatment and the patients were also given alternative methods of other treatments so that the patients has information about the illness and therapy that doctors would do. If communication between patients and doctors is effective, it could prevent medical malpractice.